MR elastography-based staging of liver fibrosis in Fontan procedure associated liver disease is confounded by effects of venous congestion. Issue 10 (October 2022) - Serai, S.D.; Tsitsiou, Y.; Wilkins, B.J.; Ghosh, A.; Cahill, A.M.; Biko, D.M.; Rychik, J.; Rand, E.B.; Goldberg, D.J.
Abstract : Aim: To compare targeted and global liver stiffness measured by magnetic resonance elastography (MRE) with liver biopsy in patients who have undergone the Fontan procedure, and to assess the relationship between liver stiffness and fibrosis stage. Materials and methods: Targeted and global liver stiffness was compared with a quantification of liver fibrosis measured by percentage of Sirius Red (%SR) staining of biopsy samples. MRE values were compared with three other biopsy-scoring methods: Ishak, Scheuer/Ludwig-Batts/Metavir, and congestive hepatic fibrosis score (CHFS). Additionally, in patients who had two or more MRE studies, global liver stiffness was compared for longitudinal assessment. Results: Thirty-four patients were included in the study, with a mean age of 16.2 years. There was no statistically significant correlation between MRE-derived liver stiffness and Ishak score, Metavir score, %SR staining, and CHFS score. Twenty patients had multiple MRE studies, with a mean age of 16.5 years, and these showed a statistically significant increase in mean liver stiffness from 3.72 to 4.68 (26% increase) within an average period of 24 months. Conclusions: The lack of correlation of liver stiffness with fibrosis stage observed in this study indicates that the effects of venous congestion in Fontan patients can confound the use of liver stiffness as a biomarker for fibrosis as assessed by percentage of SR staining, Ishak score, Metavir score, and CHFS score. These results provide motivation for further development of magnetic resonance imaging-based biomarkers to increase the specificity in the assessment of Fontan-associated liver disease. A steady increase in liver stiffness observed in these patients may be useful for longitudinal follow-up of liver health. Highlights: Our study indicates that the effects of venous congestion in Fontan patients can confound the use of liver stiffness as a biomarker for fibrosis. In the setting of Fontan, studies of the diagnostic performance of MR Elastography for staging liver fibrosis can be unreliable. A steady increase in liver stiffness observed in patients with Fontan may be useful for longitudinal follow-up of liver health.